INFLUENCE OF PRODUCT ATTRIBUTES ON CONSUMER PURCHASE DECISIONS: A STUDY OF PALM SUGAR PRODUCTS IN RAMBAH TENGAH BARAT VILLAGE - Albafery, Albafery (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
Consumers seek quality in products, especially in food items with perceived health benefits. This research examines how product attributes influence consumer purchase decisions and purchase interest in palm sugar products in Rambah Tengah Barat Village. Using a sample of 35 respondents selected through purposive sampling, data were gathered via questionnaires and analyzed with Partial Least Squares (PLS) structural equation modeling. Results indicate that purchase interest mediates the relationship between product attributes and purchasing decisions, underscoring the importance of quality product attributes in driving consumer satisfaction and purchase decisions. Key attributes influencing consumer choices include health benefits, absence of preservatives, aroma, cleanliness, packaging, solubility, color, taste, and shape. Palm sugar producers should consider enhancing these attributes to meet consumer expectations and boost competitiveness. Keywords: Consumer Purchase Decision, Product Attributes, Palm Sugar, Purchase Interest, Consumer Behavior